Evaluation of an educational telephone intervention strategy to improve non-screening colonoscopy attendance: A randomized controlled trial - Seoane, Agustín (World J Gastroenterol, 2020)
BACKGROUND: Colonoscopy attendance is a key quality parameter in colorectal cancer population screening programmes. Within these programmes, educative interventions with bidirectional contact carried out by trained personnel have been proved to be an important tool for colonoscopy attendance improvement, and because of its huge clinical and economic impact, they have been widely implemented. However, outside of this population programmes, educative measures to improve colonoscopy attendance have been poorly studied and no navigation interventions are usually performed. AIM: To investigate the clinical and economic impacts of an educational telephone intervention on colonoscopy attendance outside colorectal cancer screening programmes. METHODS: This randomized controlled trial included consecutive patients referred to colonoscopy from primary care centres from November 2017 to May 2018. The intervention group (IG) received a telephone intervention, while the control group (CG) did not. Patients assigned to the IG received an educational telephone call 7 d before the colonoscopy appointment. The intervention was carried out by two nurses with deep endoscopic knowledge who were previously trained for a telephone educational intervention for colonoscopy. The impact on patient compliance with preparedness protocols related to bowel cleansing, anti-thrombotic management, and sedation scheduling was also evaluated. A second call was conducted to assess patient satisfaction. Intention-to-treat (ITT) and per-protocol (PP) analyses were performed. RESULTS: A total of 738 and 746 patients were finally included in the IG and CG respectively. Six hundred thirteen (83%) patients were contacted in the IG. The non-attendance rate was lower in the IG, both in the ITT analysis (IG 8.4% vs CG 14.3%, P < 0.001) and in the PP analysis (4.4% vs 14.3%, P < 0.001). In a multivariable analysis, belonging to the control group increased the risk of non-attendance in both, the ITT analysis (OR 1.81, 95%CI: 1.27 to 2.58, P = 0.001) and the PP analysis (OR 3.56, 95%CI: 2.25 to 5.64, P < 0.001). There was also a significant difference in compliance with preparedness protocols [bowel cleansing: IG 61.7% vs CG 52.6% (P = 0.001), antithrombotic management: IG 92.5% vs CG 62.8% (P = 0.001), and sedation scheduling: IG 78.8% vs CG 0% (P ≤ 0.001)]. We observed a net benefit of €55600/year after the intervention. The information given before the procedure was rated as excellent by 26% (CG) and 51% (IG) of patients, P ≤ 0.001. CONCLUSION: Educational telephone nurse intervention improves attendance, protocol compliance and patient satisfaction in the non-screening colonoscopy setting and has a large economic impact, which supports its imple-mentation and maintenance over time.